FORMIC ACID PRODUCTION VIA GLUCOSE OXIDATION ROUTE - Fauzan Mahendraputra S, Naafi
Nowadays, formic acid (HCOOH) application is getting concern as hydrogen carrying liquid (= a liquid that is easily processed to release/carry hydrogen). Research and study about production formic acid from renewable materials need to be done to meet the needs of formic acid which takes into sustainability aspects. Glucose-based renewable formic acid has the potential to be produced in Indonesia which has abundant renewable natural resources. Previous research has shown that glucose (C6H12O6) can be quantitatively converted to 6 formic acid molecules through oxidation by hydrogen peroxide (H2O2), an expensive oxidizing agent, at low temperature and alkaline conditions. This process can be applied to commercial technology if only the hydrogen peroxide reagent replaced with a combination of air oxygen plus an oxidation catalyst. This study aims to obtain a suitable manganese-ion and cobalt-ion homogeneous catalyst that is suitable for autoxidizing (= an oxidizing with air oxygen) glucose into formic acid. The manganese(ii) pyrophosphate (Mn2P2O7) and cobalt(ii) pyrophosphate (Co2P2O7) salts can totally disolve to form complexes solution respectively with ratio of Mn2P2O7 : K4P2O7 valued 1,6 : 100 and Co2P2O7 : K4P2O7 valued 6,3 : 100 and with potassium pyrophosphate (K4P2O7) concentration valued 0,22 M dan 0,37 M. Based on the qualitative test of catalyst autoxidation, the potential catalyst for the glucose otoxidation reaction are : 1) Co2P2O7 complexes solution. 2) Mixture of Mn2P2O7 and Co2P2O7 complexes solution, 3) Manganese(ii) formate in pH >8 solution. 0,32 mol Glucose (230 g/L) autoxidation reaction with Co2P2O7 complexes solution as catalyst (mol Co2+: mol glucose = 2%) yielded 33.75 mmol of formic acid, so the formic acid yield is 1,75%-mol based on theoritical yield of 6 mol formic acid from 1 mol glucose.